Percutaneous Coronary Intervention in Single Coronary Ostium Presented with STEMI: A Case Report - Jefri Jefri; Vickry Wahidji (Jambura Medical and Health Science Journal, 2022)
Introduction: Coronary artery anomalies presenting with ST-segment elevation myocardial infarction (STEMI) are uncommon and often are challenging to manage. We report a case of a successful percutaneous coronary intervention (PCI) of the right coronary artery (RCA) in a patient who presented with inferior STEMI and an anomaly of the left and right coronary arteries with a single coronary ostium in the right sinus of Valsalva.Case: Male, 71 years old, was admitted to the emergency department with 8 hours onset of chest pain. The patient was diagnosed with STEMI Inferior 8 hours of onset Killip I TIMI score 5. The patient was given a dual loading antiplatelet, high-dose nitrate and statin, then we planned him for primary PCI. Primary PCI was performed on the right transradial through the single osteal coronary artery from the right sinus Valsalva. We got the TIMI flow 3 without other complications during the action.Discussion: It is frequently difficult to identify the culprit lesion during primary PCI. The course of the anomalous vessel and the culprit lesion are clear often; the revascularization procedure hides several pitfalls.Conclusion: Coronary artery anomalies presenting with STEMI are uncommon but often challenging. Percutaneous coronary intervention is considered the first choice in patients with coronary anomaly presented with STEMI.